Genome-Wide Identification and Comparative Analysis of WOX Genes in Four Euphorbiaceae Species and Their Expression Patterns in Jatropha curcas - Wang, Zhanjun; Cai, Qianwen; Xia, Haimeng; Han, Bingqing; Li, Minhui; Wang, Yue; Zhu, Minhui; Jiao, Chunyan; Wang, Dandan; Zhu, Junjie; Yuan, Wenya; Zhu, Di; et al. (Frontiers in Genetics, 2022)
WUSCHEL-related homeobox (WOX) transcription factor is widely distributed in plants and plays important regulatory roles in growth and development processes such as embryonic development and organ development. To analyze the regulation of the WOX gene family members in four Euphorbiaceae species, a series of bioinformatics methods were used to analyze the structure of the WOX genes, as well as exploring their genetic relationships. A genome-wide survey identified 59 WOX genes, namely, 20, 10, 18, and 11 genes in Hevea brasiliensis (H. brasiliensis), Jatropha curcas (J. curcas), Manihot esculenta (M. esculenta), and Ricinus communis (R. communis), respectively. Phylogenetic analysis revealed that these WOX genes could be clustered into three clades, namely ancient, intermediate and modern clades, and they were closely related. Then, gene structure and conserved motif analyses further supported the finding that the WOX genes were conserved within each phylogenetic clade. These results provide information on the relationships among WOX genes in the four Euphorbiaceae plant species. Obviously, WOX genes in H. brasiliensis and M. esculenta were more closely related as were those in J. curcas and R. communis. Additionly, the presence of various cis-acting regulatory elements in the promoters of J. curcas WOX genes (JcWOXs) suggested that these genes have different functional roles. Differential expression profiling of various JcWOXs in seeds further confirmed this speculation and revealed that two JcWOX genes (JcWOX6 and JcWOX13) are pivotal during plant growth and development. According to Quantitative real-time PCR (qRT-PCR) analysis, we found that the JcWOX11 gene plays an indispensable role in the regulation of plant callus. The present study reports the comprehensive characteristics and relationships of WOX genes in four Euphorbiaceae plant species and provides new insights into their characterization.